(untitled) (Journal of Contemporary Issues in Accounting, 2022)
This study examined the effect debt servicing on economic development in Nigeria. The objective is to determine the effect of external and domestic debt servicing on per capita income of Nigerians. Secondary data were sourced from Central Bank of Nigeria (CBN) statistical bulletin and Debt Management Office (DMO) from 2001 to 2020 (period of 20 years). The statistical tool used for data analysis was multiple regression method. The result of test of the hypothesis revealed that debt (external and domestic) servicing has an insignificant effect on per capital income in Nigeria in the short-run, while in the long-run debt (external and domestic) servicing has a significant effect on per capital income in Nigeria. This proves the point that debt as a means to finance fiscal policies of the government are better used for capital expenditure which are probable to affect long term economic plans like infrastructure-financing that spurs productive capacity of citizens and their income in the long run. Based on the finding, the study recommends that, the Nigerian government should ensure that more debt finance should be channeled towards infrastructure development in order to stimulate more short term impacts of the borrowings on the income of Nigerians against the backdrop of short term burden, debt servicing payments pose on per capital income, since it leaves little funding available for recurrent expenditures that are short term stimulants of economic growth and income of citizens.